2020
DOI: 10.3390/antibiotics9100680
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Carbapenemase-Producing Enterobacterales Infection or Colonization in a Korean Intensive Care Unit: A Case–Control Study

Abstract: The purpose of this study is to identify the factors related to the infection and/or colonization of carbapenemase-producing Enterobacterales (CPE) based on clinical and microbiological data for patients in the intensive care unit (ICU). All patients admitted to medical ICU were screened for CPE on admission and weekly, and this 1:2 case–control study included patients with CPE identified by screening or clinical cultures from 2017 to 2018. The clonal relatedness was evaluated by pulsed-field gel electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…This is in line with Mantzarlis et al [ 35 ], who found similar results for the two different ways to account for antibiotic exposure. In addition, we were not able to demonstrate an effect of other antibiotic classes often associated with CR or/ and ESBL Kp in the literature [ 15 ], such as carbapenems [ 16 , 21 , 36 , 37 , 38 ], fluoroquinolones [ 12 , 13 , 39 ], and extended-spectrum cephalosporins [ 13 , 14 , 39 ]. In our opinion, this may be due to the different study designs or outcomes of these studies, mostly investigating temporal trend association or colonization, together with infections.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with Mantzarlis et al [ 35 ], who found similar results for the two different ways to account for antibiotic exposure. In addition, we were not able to demonstrate an effect of other antibiotic classes often associated with CR or/ and ESBL Kp in the literature [ 15 ], such as carbapenems [ 16 , 21 , 36 , 37 , 38 ], fluoroquinolones [ 12 , 13 , 39 ], and extended-spectrum cephalosporins [ 13 , 14 , 39 ]. In our opinion, this may be due to the different study designs or outcomes of these studies, mostly investigating temporal trend association or colonization, together with infections.…”
Section: Discussionmentioning
confidence: 99%
“…First, the analysis was performed in a single tertiary care hospital, and most of the enrolled patients had undergone a liver transplantation. Because such cases involve the use of several different medical devices, require mechanical ventilation, and have a higher risk of exposure to antimicrobial agents and thus they have a greater risk of CPE colonization than the general population [11,12]. Second, we did not perform genetic analyses of the CPE strains to compare the isolates from close contact patients and index cases.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, admission to ICU is a risk factor for acquiring these strains, probably due to several reasons, such as long-term ventilator use [ 93 ], antibiotic pressure or presence of CREs or plasmids in the ICU area. A recent case-control study performed in Korea [ 94 ] showed that pneumonia/chronic pulmonary disease, previous fluoroquinolone use and previous use of nasogastric tube were the significant risk factors for CRE infection or colonization in ICU-admitted patients, although no OXA-48-like CRE were identified in their study.…”
Section: Oxa-48 Cre Outbreaks In Spainmentioning
confidence: 99%